Gestão da educação especial na diretoria de ensino região santos. - Quintairos, Matilde Perez (2015)
The historical changes in the Special Education sense point out the subject of study and evidently, a very complex aim of political public which indicates at least two huge challenges: The guarantee of the total right of Education to the Special Education target public (PAEE) in ways which this rights may be affected among all modifications and noticeably, the improvement of concepts and nomenclatures used in this knowledge base. In this sense, the aim of this study is to contribute to the reflection about the legal apparatus, development and implementation of political public in the Special Education, getting an inclusive perspective, more specifically on the attendance background to the PAEE in Public Schools from Sao Paulo State, confined by ¿Diretoria de Ensino ¿ Região Santos¿. The methodological approach, perceive on the documental and bibliographic research, related to the theme, such as an investigation of Terms for the adjustment of Conduct (TAC) from the Public Ministry of São Paulo State. The study demands to seize some procedures, whereby an intermediate provider¿s management implements an inclusive political of Special Education, among its specific context of action, some of it obstacles and eventual gaps in guarantee of the right of Education to this specific people. In conclusion, we noticed that there were some progresses on the political action, mainly for the significant action from the Public Ministry, remarkably, an external management department. Nevertheless, there will still be a long way to course on the Political of Special Education Inclusive implementation on this analysed context.